The Impact Of Instructional Scaffolding Strategy In Collection Chemistry To The Fourth Scientific Stage - Kamal Mohammed, Mohammed; Aziz Al Amiry, Zainab (Opción, 2019)
The present study aimed at knowing “the effect of the educational support strategy on the achievement of chemistry among fourth grade students”. To achieve this, the researcher chose Dhulnnurain secondary school in Baghdad governorate of Karkh / 3. The research sample reached (56) students from the fourth grade (28). The researcher formulated (130) behavioral objectives within the levels (remembering, assimilation, application and analysis) ac- cording to Bloom’s classification of the field of knowledge, the researcher has prepared an achievement test consisting of (20) objective paragraphs of the type of selection The multiplicity of his psychometric properties has been as- certained, following with The results of the study were found to be superior to the experimental group students who studied chemistry according to the teaching stand strategy in the achievement test.